Accumulation of Basic Amino Acids at Mitochondria Dictates the Cytotoxicity of Aberrant Ubiquitin - Braun, Ralf J.; Sommer, Cornelia; Leibiger, Christine; Gentier, Romina J.G.; Dumit, Verónica I.; Paduch, Katrin; Eisenberg, Tobias; Habernig, Lukas; Trausinger, Gert; Magnes, Christoph; Pieber, Thomas; Sinner, Frank; et al. (Cell reports (Cambridge), 2015)
Neuronal accumulation of UBB+1, a frameshift variant of ubiquitin B, is a hallmark of Alzheimer’s disease (AD). How UBB+1 contributes to neuronal dysfunction remains elusive. Here, we show that in brain regions of AD patients with neurofibrillary tangles UBB+1 co-exists with VMS1, the mitochondrion-specific component of the ubiquitin-proteasome system (UPS). Expression of UBB+1 in yeast disturbs the UPS, leading to mitochondrial stress and apoptosis. Inhibiting UPS activity exacerbates while stimulating UPS by the transcription activator Rpn4 reduces UBB+1-triggered cytotoxicity. High levels of the Rpn4 target protein Cdc48 and its cofactor Vms1 are sufficient to relieve programmed cell death. We identified the UBB+1-induced enhancement of the basic amino acids arginine, ornithine, and lysine at mitochondria as a decisive toxic event, which can be reversed by Cdc48/Vms1-mediated proteolysis. The fact that AD-induced cellular dysfunctions can be avoided by UPS activity at mitochondria has potentially far-reaching pathophysiological implications. [Display omitted] •UBB+1 co-exists with the UPS component VMS1 in neurofibrillary tangles•UBB+1 accumulation impairs the UPS and mitochondria, triggering cell death•UBB+1 causes accumulation of basic amino acids at mitochondria•Vms1 reverts UBB+1-triggered basic amino acid accumulation and cell death Braun et al. demonstrate that basic amino acid accumulation at mitochondria is a decisive toxic event upon cellular accumulation of UBB+1, an Alzheimer’s-disease-associated ubiquitin variant. Triggering the mitochondrion-specific branch of the ubiquitin-proteasome system is sufficient to prevent UBB+1-triggered cytotoxicity, which has potentially far-reaching pathophysiological implications.